Analisis Kadar Arsen (As) pada Sayur Kubis Hijau (Brassica oleracea L.) Pasca Erupsi Gunung Sinabung - Cahyady, Boby; Taufik, Muhammad; Suharman, Suharman (ALCHEMY, 2021)
ount Sinabung has had an impact on the lives of surrounding farmers after the eruption. One of the negative impacts is the exposure of plants and animals around them to dangerous chemical compounds, especially heavy metals. This work aimed to analyze the levels of arsenic (As) in green cabbage (Brassica oleracea L.) which was exposed after two months of the eruption. The sampling method was done using a simple random sampling technique at five points. The digestion process was carried out using hydrochloric acid and nitric acid. Arsenic analysis was performed using the atomic absorption spectroscopy (AAS) at 193.7 nm with vapor hydride generation accessories. Concentration of arsenic exposed to green cabbage at five sampling points was 0.4102, 0.4936, 0.4501, 0.6425, and 0.6534 mg/Kg. The results obtained were lower than the maximum limit of arsenic contamination in vegetables, namely 1.0 mg/Kg based on SNI No. 7387:2009.Keywords: arsenic, Brassica oleracea L, AAS, SNI, Mount SinabungGunung Sinabung memiliki pengaruh kepada kehidupan petani di sekitarnya pasca erupsi. Salah satu dampak negatifnya adalah terpaparnya tumbuhan dan hewan di sekitar terhadap senyawa kimia yang berbahaya, khususnya logam berat. Penelitian ini bertujuan untuk menganalisis kadar arsen (As) yang terdapat pada sayur kubis hijau (Brassica oleracea L.) yang terpapar setelah dua bulan erupsi. Pengambilan sampel dilakukan dengan menggunakan teknik simple random sampling di lima titik. Proses destruksi dilakukan dengan menggunakan asam klorida dan asam nitrat. Analisis arsen dilakukan dengan menggunakan atomic absorption spectroscopy (AAS) pada panjang gelombang 193,7 nm yang dilengkapi vapour hydride generation accessories. Kadar arsen yang terpapar pada sayur kubis hijau pada lima titik pengambilan sampel berturut turut sebesar 0,4102; 0,4936; 0,4501; 0,6425, dan 0,6534 mg/Kg. Kadar arsen yang diperoleh lebih rendah dari batas maksimum cemaran arsen dalam sayuran yakni 1,0 mg/Kg berdasarkan SNI No. 7387:2009.Kata kunci: arsen, Brassica oleracea L., AAS, SNI, Gunung Sinabung